26. OPTIMIZING SURGICAL ANTIBIOTIC PROPHYLAXIS COMPLIANCE OF MEDICAL STAFF AT THU DUC CITY HOSPITAL, HO CHI MINH CITY IN 2021 (Vietnam Journal of Community Medicine, 2022)
Objects: This study aimed to assess the status and associated factors effecting the compliance withregulations on surgical antibiotics prophylaxis at Thu Duc city hospital in 2021.Methods: A descriptive cross-sectional study was conducted among 270 medical records of patientswho had had surgery indications and underwent clean, clean-contaminated procedures at Surgicaldepartments of the hospital from January to June 2021.Results: The rate of compliance with all five criteria on the use of prophylactic antibiotics at thehospital was only 17%. While most cases had appropriate indications, route of administration anddosage (the rates were 92.2%, 95.5% and 85.9%, respectively), the appropriate antibiotics election ratewas only 77%. Moreover, the proportion of compliance with medication regimens was significantlylow at 17.8%. The adherence rate was higher in patients who were over 60 years old, had cleancontaminated surgery, emergency surgery and length of hospital stay more than one day before andive days after surgery.Conclusions: Improving the antibiotic management program at the hospital is very necessary for thecurrent period, focusing on monitoring the use of antibiotics and training doctors on rational, safeand effective antibiotic use.
Keywords: Compliance, Prophylactic antibiotics, Thu Duc City Hospital.